Pengaruh Kemudahan, Kemanfaatan, dan Keamanan Terhadap Keputusan Transaksi Menggunakan QRIS: Studi Masyarakat Solo Raya - Ilya Nur Rahmawati; Budi Sukardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Current developments in the field of industrial technology encourage people to get used to using digital transactions, which are often called financial technology (fintech). This research aims to find out how convenience influences the decision to use digital money (QRIS), how usefulness influences the decision whether to use digital money (QRIS), and how security influences the decision to use digital money (QRIS). The population in this study was the Solo Raya community, questionnaires were distributed to 150 respondents. The data was tested using respondent descriptions, evaluation of the outer model, and evaluation of the inner model. The findings show that usefulness and safety have a significant influence on the decision to use QRIS. However, convenience does not influence the decision to use QRIS.